Development of creativity in concurrent engineering teams - Aslani, Alireza; Helo, Petri; Naaranoja, Marja (Scientific Research Publishing, 2012)
The development of successful new products is today of challenge to most consumer product companies. They have to short their response time, pushing their development processes to move faster while keeping on competitive prices and quality. These caused companies are forced to find effective and innovative approaches as work methods to overcome to pressures. Concurrent Engineering (CE) is one of the approaches to address these managerial and manufacturing dilemmas in new product projects. The basic premise of CE revolves around team working. However, most of the managers especially project managers face with problems when they want to promote teamwork culture, especially in conditions that the project faces with complicated problems. In this condition, a creative team consists of members from different levels of the organizational hierarchy must be shaped. There are always barriers in group meetings that influence growth and diffusion of creative solutions and would be reduced by using creativity and innovation techniques. The first purpose of this study is to identify the effective criteria in success of creative meetings in CE projects. Next, the prioritization of each factor has been analyzed and ranked respectively. Finally, based on the results of previous research of the authors, the useful group creativity and innovation techniques related with team work meetings in CE projects have been ranked by using the Analytic Hierarchy Process (AHP) approach.
Keywords: concurrent engineering; decision making; uncertainty; teamwork; creativity techniques; AHP; leadership (activity); teamwork; creativity; problem solving; teams; groups; group work; strategic leadership; cooperation (general); working life; fi=Tuotantotalous|en=Industrial Management|